The Relationship between Product and International Diversification: The Effect of Asset Dispersion and Asset Diversity on Firm Performance - MUZYRYA, Yulia (Institutional Knowledge at Singapore Management University, 2010)
There is little consensus on the diversification-performance relationship in the diversification literature. We aim to contribute to this literature by looking simultaneously at product and international diversification and the relationship between both. Furthermore, we distinguish theoretically and empirically between two different components of any diversification strategy, i.e. the degree of diversification and the type of diversification. We test our hypotheses on panel data covering 115 firms. We find that the dispersion of a firm’s activities, both internationally and in different product markets, results in higher levels of performance. Contrary, we find that higher levels in the diversity of the firm’s activities are negatively associated with firm performance. We also find evidence that firms can disperse their activities simultaneously in different product and geographic markets, however, they face trade-offs when it comes to having more diversity in their activities in different geographic and product markets. Our findings help us explain some of the apparent contradictions in the diversification literature and they offer guidance to managers on how to pursue an optimal diversification strategy.